PENGEMBANGAN MEDIA AJAR BERBENTUK AUDIOVISUAL BERBANTUAN POWTOON PADA PEMBELAJARAN MATEMATIKA BANGUN RUANG SISWA KELAS V SEKOLAH DASAR - Sartika Eka Fitri Lubis (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
When teachers teach in class, some students have difficulty understanding math lessons and get bored and find them difficult. To overcome this, new and interesting teaching media are needed that can increase student creativity, one of which uses audiovisual media assisted by Powtoon. The RnD development method is used to test the effectiveness of this media, and the results show that the teaching media developed are suitable for use in class, with the description of material validation achieving 3.76, media validation achieving 3.7, display quality getting 3.8 achievements and effectiveness getting 3.87 achievements.